2018
DOI: 10.33373/pythagoras.v7i2.1336
|View full text |Cite
|
Sign up to set email alerts
|

Berpikir Impulsif Dalam Komunikasi Matematis Siswa Sekolah Menengah Pertama

Abstract: Abstrak: Tujuan penelitian ini untuk menelusuri komunikasi matematis siswa kelas VII SMP berdasarkan gaya kognitif impulsif. Jenis penelitian ini adalah penelitian kualitatif deskriptif. Subjek dalam penelitian ini adalah siswa kelas VII SMP N 2 Gubug Pemilihan subjek penelitian dengan teknik purposive sampling,  Teknik keabsahan data yang digunakan dengan triangulasi metode. Analisis data mengikuti konsep Miles dan Huberman dengan proses: (1) Reduksi data, (2) Sajian data; dan (3) Penarikan kesimpulan dan ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
3
1
0
1
Order By: Relevance
“…This indicates that the written mathematics communication of the SR subject related to the information on the questions was accurate and complete. These results are in accordance with Shodiqin's [16] research that reflective students are able to write down things that are known and asked completely and correctly. Following are the interviews of researchers with SR subjects related to information that is known and asked in open-ended questions.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This indicates that the written mathematics communication of the SR subject related to the information on the questions was accurate and complete. These results are in accordance with Shodiqin's [16] research that reflective students are able to write down things that are known and asked completely and correctly. Following are the interviews of researchers with SR subjects related to information that is known and asked in open-ended questions.…”
Section: Resultssupporting
confidence: 91%
“…Based on the above analysis, communication both oral and written of SI subject can be said inaccurate, complete and fluent in terms of mentioning the steps for solving open-ended questions. This is in accordance with the results of Shodiqin's [16] research that impulsive students can complete the completion steps and were able to communicate them completely and clearly even though there are still some mistakes.…”
Section: ) (Cl2)supporting
confidence: 90%
“…Based on the analysis of the lecturer's response questionnaire, an average score of 3.37 was obtained which was also in the practical category. This study was supported by [26] found that the use of the Geogebra program had a good effect in terms of learning outcomes and motivation, research [27] found that learning using mathematics teaching materials in the form of tabloids assisted by Wolfram Mathematica software with a contextual approach was better than conventional learning on integral material and also supported by [30] that the use of software, especially Geogebra helps students to focus on the material, and they also admit that they can visualize graphics well using Geogebra.…”
Section: Discussionsupporting
confidence: 64%
“…Sehingga siswa impulsif tidak perlu memikirkan secara mendalam untuk dapat memahami masalah. Hal ini sejalan dengan penelitian Shodiqin & Zuhri (2018), siswa impulsif mampu menentukan hal-hal yang diketahui dan ditanyakan, tetapi cenderung tergesa-gesa. Sebagai tambahan, penelitian yang dilakukan Cahyono dkk., (2019), dalam memahami masalah siswa impulsif menceritakan kembali informasi yang didapat menggunakan bahasa sendiri maupun mengadopsi dari soal.…”
Section: Mandalika Mathematics and Education Journal Volume 5 Nomor 2...unclassified